Deaf eyes on interpreting - Holcomb, Thomas K., 1959-; Smith, David H. (David Harry) (Washington, D.C. : Gallaudet University Press, 2018)
"As the ASL-English interpreting field has become professionalized, there is a growing disconnect between interpreters and the Deaf consumers they serve. Whereas interpreting used to be a community-based practice, the field is growing into a research-based profession that begins in a classroom rather than in the Deaf community. Despite the many gains being made in the interpreting services profession, with an emphasis on the accuracy of the interpreted work, the perspectives of Deaf individuals are rarely documented in the literature. Opportunities for enhanced participation and full inclusion need to be considered in order for Deaf people to best represent themselves to the hearing, nonsigning public as competent and intelligent individuals. Deaf Eyes on Interpreting brings Deaf people to the forefront of the discussions about what constitutes quality interpreting services. The contributors are all Deaf professionals who use interpreters on a regular basis, and their insights and recommendations are based on research as well as on personal experiences. These multiple perspectives reveal strategies to maximize access to interpreted work and hearing environments and to facilitate trust and understanding between interpreters and Deaf consumers. Interpreter educators, interpreting students, professional interpreters, and Deaf individuals will all benefit from the approaches offered in this collection"--
"As the ASL-English interpreting field has become professionalized, there is a growing disconnect between interpreters and the Deaf consumers they serve. This books brings Deaf people to the forefront of the discussion about what constitutes quality interpreting services"--
Part 1: Seeing the issues through deaf eyes. The importance of storytelling to address deaf disempowerment / Trudy Suggs -- Deaf dream team : DEAM approaches to interpreting / Thomas K. Holcomb -- Accountability and transparency : the missing link in ensuring quality in interpreting / Chad W. Taylor, Ryan A. Shephard, and Justin "Bucky" Buckhold -- Part 2: Understanding the issues through deaf eyes. American Sign Language interpreting in a mainstreamed college setting : performance quality and its impact on classroom participation equity / John S. Pirone, Jonathan Henner, and Wyatte C. Hall -- The heart of interpreting from deaf perspectives / Kim B. Kurz and Joseph C. Hill -- ASL head movements : critical features in interpretation / Keith M. Cagle, Sharon J. Lott, and Phyllis P. Wilcox -- Whose professional reputation is at stake? A case study / Tara K. Holcomb and Aracelia Aguilar -- Harnessing social media as a tool of empowerment and change / Leala Holcomb -- Part 3: Exploring the specialized areas of interpreting through deaf eyes. Higher education : higher expectations and more complex roles for interpreters / Tawny Holmes -- Through the eyes of deaf academics : interpreting in the context of higher education / David H. Smith and Paul W. Ogden -- Case studies of international conferences : a social justice framework for interpreting / Patrick Boudreault and Genie Gertz -- Going beyond trust : protecting my integrity as a deaf academic / Thomas K. Holcomb -- Educational interpreting from deaf eyes / Amy June Rowley -- Hey listen : mainstreamed deaf children deserve more! / Fallon Brizendine -- It takes two to tango : crafting a flawless partnership in the corporate world / Sam Sepah -- Community healthcare interpreting / Susan Gonzalez, Lewis S. Lummer, Cynthia J. Plue, and Marta Ordaz -- Part 4: Moving forward with deaf eyes. On resolving cultural conflicts and the meaning of deaf-centered interpreting / Wyatte C. Hall -- The ingredients necessary to become a favorite interpreter / Marika Kovacs-Houlihan -- Effectively interpreting content areas utilizing academic ASL strategies / Christopher A.N. Kurz, Kim B. Kurz, and Raychelle Harris -- Your name what? You from where? / Naoim Sheneman.
Includes bibliographical references and index.
Keywords: Interpreters for deaf people; Translating and interpreting; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; LANGUAGE ARTS & DISCIPLINES / Sign Language